Climate change and dust storms in Iraq / 'Baghdad', case study - محمد, فاطمة جاسم (Journal of Economics and Administrative Sciences, 2015)
A dust storm in Iraq is a climatic phenomenon common in arid and semi-arid regions . The frequency of the occurrence has increased drastically in the last decade and it is increasing continuously .Baghdad city like the rest of Iraq is suffering from the significant increase in dust storms . In this research , the study of the phenomenon of dust storms for all types (Suspended dust , rising dust , dust storm) , and its relationship with some climate variables (Temperature , rainfall ,wind speed) .The statement of the impact of climate change on this phenomenon to Baghdad station  for the period (1981 – 2012) . Time series has been addressing the phenomenon of storms and climate variables for the time period under study, during which Iraq faced three wars affected the growing phenomenon occurring factors , missing values ​​were estimated and identification of multiple outliers within the existing time series of phenomena and  climate variables , the study found that climate change (the direction of rainfall downward,  the direction of the temperature to rise, the direction of wind speed to rise) paid to the growing phenomenon of dust storms in that station studied and showed the relationship of these variables to this phenomenon (by type) through regression models